Great Powers in the Changing International Order - Bisley, Nick (New Delhi Viva Books (Pvt.) Ltd., 2016)
What does it mean to be a great power? What role do great powers have in managing international order, and is that role still relevant in a globalizing world? Are new great powers likely to emerge? If so, to what effect? Addressing this set of questions, Nick Bisley provides a historically informed and theoretically grounded analysis of the part that great powers play in contemporary world politics. Bisley traces the idea of great power management from its origins in European history to the present day. Arguing that the idea that great powers have a special responsibility for maintaining international order is badly out of step with contemporary circumstances, he offers an intriguing conclusion about the nature of the international system.
Include Bibliography and Index.
Keywords: Great powers -- International relations